Supported molten-salt membranes for carbon dioxide permeation. Issue 21 (17th May 2019) - Mutch, Greg A.; Qu, Liu; Triantafyllou, Georgios; Xing, Wen; Fontaine, Marie-Laure; Metcalfe, Ian S.
Abstract : First review of supported molten-salt membranes highlighting materials challenges, mechanistic development and manufacturing opportunities towards energy applications. Abstract : Membranes for selective carbon dioxide permeation are likely to be important devices in future separation processes relevant to the energy industry. Here we review the current state of research into a particular class of carbon dioxide permeable membrane: the supported molten-salt membrane. Such membranes rely upon ionic transport pathways through a molten salt with or without electronic and ionic transport contributions from the inorganic support. This variety of transport pathways allows a considerable degree of flexibility in membrane design. The use of molten salts permits high temperature operation and produces highly permeable membranes with theoretically infinite selectivity. Here we review work on materials selection and properties, likely permeation mechanisms and the role and control of membrane microstructure. We review results from permeation experiments and discuss the importance of materials compatibility and the role of interfacial processes in membrane degradation. We finish with comments on prospects for scale-up and commercialisation.